Non-parental Care Arrangements, Parenting Stress, and Demand for Infant-Toddler Care in China: Evidence From a National Survey - Hong, Xiumin; Zhu, Wenting; Luo, Li (Frontiers in Psychology, 2022)
The present study examined the patterns and characteristics of nonparental child care arrangements for Chinese very young children before they enter preschool, and the extent to which families’ utilization of nonparental child care influenced parenting stress. A total of 3,842 Chinese parents of infants and toddlers were selected from 10 provinces to participate in the present study. The results indicated that: (1) Chinese families relied heavily on grandparents to care for their children; (2) A set of family demographics predicted the utilization of nonparental child care arrangements, including parents’ educational level, household income, labor force participation, and maternal age; (3) There existed a clear parental preference for publicly-funded, affordable, and high-quality child care services; and (4) Families’ use of nonparental child care was generally not linked to parenting stress. These findings will shed light on the development of infant-toddler nonparental child care system in the Chinese socio-cultural context.